2014
DOI: 10.1016/j.hemonc.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus and Hodgkin lymphoma in Jordan

Abstract: The epidemiology of HL in Jordan and some developing countries is approaching that of developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 33 publications
7
14
2
1
Order By: Relevance
“…The highest incidence of EBV positivity was noted in India and Saudi Arabia (82 and 88%, respectively) [23, 24]. The lowest expression of EBV was noted in Jordan (43.6%) [25]. Our results were comparable with those of another study conducted in Pakistan depicting 50% expression of EBV in Hodgkin lymphoma [26].…”
Section: Discussionsupporting
confidence: 83%
“…The highest incidence of EBV positivity was noted in India and Saudi Arabia (82 and 88%, respectively) [23, 24]. The lowest expression of EBV was noted in Jordan (43.6%) [25]. Our results were comparable with those of another study conducted in Pakistan depicting 50% expression of EBV in Hodgkin lymphoma [26].…”
Section: Discussionsupporting
confidence: 83%
“…A recent report has shown that, in the Republic of Korea, a shift from pattern II to pattern III has occurred over a period of 31 years, reflecting the impact of social and economic development in this country 4 . Similar studies in other countries, however, have identified a mixed pattern (Pattern II with a bias to Pattern I or Pattern III, depending on the influence of more pronounced poorer or improved socioeconomic conditions) 5 12 .…”
Section: Introductionsupporting
confidence: 71%
“…This result is in the range of reported positivity in European countries [13,18,21,26]. EBV positivity varies depending on geographic area and ethnicity: 17% in the Czech Republic, 79% in Kenya, 78% in India, 52% in Zambia, and 46% in Jordan [10,11,17,18,21,27]. The EBV rate in cHL has been evolving over time.…”
Section: Discussionmentioning
confidence: 57%
“…The presence of EBV in cHL varies from 13 to 79% depending on the series. It is associated with younger or older age (<10 or > 50 years ), lower economic status, ethnicity (Hispanic, African population) [8,9], MC histology, and immunosuppression [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The presence of in situ EBV has been shown to have no prognostic impact except for patients > 50 years of age [24].…”
Section: Introductionmentioning
confidence: 99%